The 25 sitcoms that changed television : turning points in American culture - Westengard, Laura; Barlow, Aaron, 1951- (Praeger, 2018)
This book spotlights the 25 most important sitcoms to ever air on American television--shows that made generations laugh, challenged our ideas regarding gender, family, race, marital roles, and sexual identity, and now serve as time capsules of U.S. history. -- Provided by publisher.
Includes index.
Keywords: Situation comedies (Television programs) -- United States.; Television broadcasting -- Social aspects -- United States.; Comédies de situation -- États-Unis.; Télévision -- Aspect social -- États-Unis.; PERFORMING ARTS -- Reference.; Situation comedies (Television programs); Television broadcasting -- Social aspects; United States